Canada : Financial Sector Assessment Program-Impact on the Insurance Sector of a Low Interest Rate Environment-Technical Note. (IMF Staff Country Reports; Country Report, 2014)
This paper discusses Canada's Financial Sector Assessment Program (FSAP) impact on the insurance sector of a low interest rate environment. It highlights that actuarial standards on valuation of liabilities require that assumed reinvestment rates take increasing account of current market rates that led to higher liabilities as low rates persisted. The note outlines the effect of Canadian accounting and actuarial standards that further increases in liabilities need to be recognized in the short term. Policy measures have been undertaken by Office of the Superintendent of Financial Institutions (OSFI) in the banking sector to address broader risks.